Was ist heute noch links? - Ladwig, Bernd (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
Traditionally left thinking hat its centre in equality, while right thinking stresses freedom. Here an approach of radical equality of chances is discussed. A “social-liberal” position is favoured and political consequences are drawn like strong interventions in the law of inheritance or the right to a fair share of paid labour.